2017
DOI: 10.1111/ijfs.13550
|View full text |Cite
|
Sign up to set email alerts
|

Milk with different somatic cells counts and the physicochemical, microbiological characteristics and fatty acid profile of pasteurised milk cream: is there an association?

Abstract: In this study, raw cow milk containing somatic cells counts (SCC) at mean levels of 39 000 cells mL À1 (low), 349 000 cells mL À1 (intermediate) and 1 297 000 cells mL À1 (high) was used for the production of pasteurised cream. Physicochemical (pH, fat and fatty acid profile) and microbiological analyses (mesophilic and psychrotrophs) were performed in the obtained creams during 30 days of refrigerated storage at 5°C AE 2. No interactions (P > 0.05) were found between SCC, storage time and the physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The levels of linoleic acid, linolenic acid, and CLA isomers were higher in cheeses produced with low SCC (Table 1), and similar results were found by Coelho et al (2017) in cow milk cream with a low SCC. Milk with different SCC presents different profiles of endogenous enzymes entailing different degrees of lipolysis, which give rise to dairy products with different characteristics (Li et al, 2014).…”
Section: Identification Of Important Input Variablessupporting
confidence: 75%
“…The levels of linoleic acid, linolenic acid, and CLA isomers were higher in cheeses produced with low SCC (Table 1), and similar results were found by Coelho et al (2017) in cow milk cream with a low SCC. Milk with different SCC presents different profiles of endogenous enzymes entailing different degrees of lipolysis, which give rise to dairy products with different characteristics (Li et al, 2014).…”
Section: Identification Of Important Input Variablessupporting
confidence: 75%
“…This study brings a significant contribution in verifying the influence of somatic cell count on the sensory acceptance and consumption intent of pasteurized milk and coalho cheese. Coelho et al, (2017) indicate that the product may be a technological alternative for using milk with a high SCC, since no significant microbiological and physicochemical changes were detected during storage for 30 days.…”
Section: Effect Of High Somatic Cell Counts On the Sensory Acceptancementioning
confidence: 99%
“…Research has shown that elevated SCC is a factor which changes the composition of the milk (Coelho et al, 2017). Geary et al ( 2013) reviewed many of these publications in their meta-analysis study.…”
Section: Correlation Between Scc and Nutritional Componentsmentioning
confidence: 99%